2012
DOI: 10.1017/s0033291712002073
|View full text |Cite
|
Sign up to set email alerts
|

Identification and management of prisoners with severe psychiatric illness by specialist mental health services

Abstract: Inreach teams identified and managed only a small proportion of prisoners with SMI. Prison-based services need to improve screening procedures and develop effective care pathways to ensure access to appropriate services. Improved identification of mental illness is needed in both the community and the Criminal Justice System to better engage with socially transient individuals who have chaotic lifestyles and complex needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 19 publications
4
67
1
1
Order By: Relevance
“…There is some evidence that mental health inreach teams identify and treat only a small proportion of prisoners with mental disorders (Bulten et al, 2009;Naidoo and Mkize, 2012;Senior et al, 2013). It is imperative to improve the screening procedures of prisoners in need of care and to promote effective care pathways to ensure appropriate access to treatment.…”
Section: Implications Of the Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some evidence that mental health inreach teams identify and treat only a small proportion of prisoners with mental disorders (Bulten et al, 2009;Naidoo and Mkize, 2012;Senior et al, 2013). It is imperative to improve the screening procedures of prisoners in need of care and to promote effective care pathways to ensure appropriate access to treatment.…”
Section: Implications Of the Findingsmentioning
confidence: 99%
“…New models of service delivery should also be investigated in the prison setting, to identify those with the greatest cost-saving effectiveness. In past studies, a relevant fraction of prisoners with an ongoing psychopathology was not detected or did not receive proper treatment (Bulten et al, 2009;Naidoo and Mkize, 2012;Senior et al, 2013). The provision of effective treatment to the prisoners with psychiatric disorders might have potentially substantial public health benefits, and possibly reduce re-offending rates.…”
Section: Pathways For Future Researchmentioning
confidence: 99%
“…Previous studies have shown how offenders with mental health problems in the CJ system are missed and better screening tools have been adopted to reduce this oversight (McKinnon et al, 2013;Senior et al, 2013;Shaw et al, 2008). Slade et al (2016) in their evaluation of the same prison found only 3% prisoners were identified with serious mental illness on reception but 33% displayed acute symptoms later in their imprisonment.…”
Section: Discussionmentioning
confidence: 99%
“…The study, undertaken in six prisons in England and that included 3492 male and female adult prisoners, concluded that only 25% of those with an SMI, defined as major depressive disorder, bipolar disorder and/or any form of psychosis, were assessed by in-reach services within a month of reception into custody. Furthermore, only 13% were actually accepted onto in-reach team case-loads for ongoing treatment (Senior et al, 2013). A much earlier study with similar methodology reported that only 23% of prisoners with SMI were identified by routine health screening upon reception into custody and that, if not identified at this stage, mental disorder was likely to remain unidentified throughout a person's time in custody (Birmingham et al, 1996).…”
Section: Current Issues In Prison Mental Healthcare In England and Walesmentioning
confidence: 99%